2016
DOI: 10.1242/jcs.179887
|View full text |Cite
|
Sign up to set email alerts
|

HSPB7 interacts with dimerized FLNC and its absence results in progressive myopathy in skeletal muscles

Abstract: HSPB7 belongs to the small heat-shock protein (sHSP) family, and its expression is restricted to cardiac and skeletal muscles from embryonic stages to adulthood. Here, we found that skeletal-muscle-specific ablation of the HspB7 does not affect myogenesis during embryonic stages to postnatal day 1 (P1), but causes subsequent postnatal death owing to a respiration defect, with progressive myopathy phenotypes in the diaphragm. Deficiency of HSPB7 in the diaphragm muscle resulted in muscle fibrosis, sarcomere dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
62
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 51 publications
(69 citation statements)
references
References 53 publications
(57 reference statements)
7
62
0
Order By: Relevance
“…5A), in agreement with Juo et al (2016) who showed that Hspb7 does not contribute directly to myogenesis. Hspb7 has been associated with autophagy but the mechanism is unclear (Vos et al, 2010).…”
Section: Characterization Of the Role Of Hspb7 In Muscle Atrophysupporting
confidence: 90%
See 4 more Smart Citations
“…5A), in agreement with Juo et al (2016) who showed that Hspb7 does not contribute directly to myogenesis. Hspb7 has been associated with autophagy but the mechanism is unclear (Vos et al, 2010).…”
Section: Characterization Of the Role Of Hspb7 In Muscle Atrophysupporting
confidence: 90%
“…Hspb7 expression is higher in mdx (a genetic model of muscular dystrophy) mice than in normal mice and is also enhanced in ageing muscle (Doran et al, 2006(Doran et al, , 2007. Recently, a skeletal muscle-specific conditional Hspb7 knockout model was reported to result in progressive myopathy (Juo et al, 2016). The role of Plekhh2 appears to be to stabilize the cortical actin cytoskeleton (Perisic et al, 2012).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations